Rqc2p and 60S ribosomal subunits mediate mRNA-independent elongation of nascent chains - Shen, Peter S. (Science, 2015)
In Eukarya, stalled translation induces 40S dissociation and recruitment of the Ribosome Quality control Complex (RQC) to the 60S subunit, which mediates nascent chain degradation. Here, we report cryoEM structures revealing that the RQC components Rqc2p (YPL009C/Tae2) and Ltn1p (YMR247C/Rkr1) bind to the 60S at sites exposed after 40S dissociation, placing the Ltn1p RING domain near the exit channel and Rqc2p over the P-site tRNA. We further demonstrate that Rqc2p recruits alanine and threonine charged tRNA to the A-site and directs elongation of nascent chains independently of mRNA or 40S subunits. Our work uncovers an unexpected mechanism of protein synthesis in which a protein—not an mRNA—determines tRNA recruitment and the tagging of nascent chains with Carboxy-terminal Ala and Thr extensions (“CAT tails”).